Synthesis and characterization of thermally stable poly(amide-imide)-montmorillonite nanocomposites based on bis(4-carboxyphenyl)-N,N'-pyromellitimide acid - M. Hajibeygi; A. Asghari; K. Faghihi (Bulletin of the Chemical Society of Ethiopia, 2013)
Two new poly(amide-imide)-montmorillonite reinforced nanocomposites containing bis(4-carboxyphenyl)-N,N'-pyromellitimide acid moiety in the main chain were synthesized by a convenient solution intercalation technique. Poly(amide-imide) (PAI) as a source of polymer matrix was synthesized by the direct polycondensation reaction of bis(4-carboxyphenyl)-N,N'-pyromellitimide acid with 4,4'-diamino diphenyl sulfone in the presence of triphenyl phosphite (TPP), CaCl2, pyridine and N-methyl-2-pyrrolidone (NMP). Morphology and structure of the resulting PAI-nanocomposite films with 10 and 20% silicate particles were characterized by FT-IR spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The effect of clay dispersion and the interaction between clay and polymeric chains on the properties of nanocomposites films were investigated by using UV-Vis spectroscopy, thermal gravimetry analysis (TGA) and water uptake measurements.DOI: http://dx.doi.org/10.4314/bcse.v27i1.10